An Anionic‐MOF‐Based Bifunctional Separator for Regulating Lithium Deposition and Suppressing Polysulfides Shuttle in Li–S Batteries. Issue 7 (15th April 2020) - Wang, Ziqi; Huang, Weiyuan; Hua, Jiachuan; Wang, Yidi; Yi, Haocong; Zhao, Wenguang; Zhao, Qinghe; Jia, Hao; Fei, Bin; Pan, Feng
Abstract: Lithium–sulfur (Li–S) batteries have been regarded as a promising energy‐storage system owing to their high theoretical energy density of 2600 Wh kg −1 and low cost of raw materials. However, the dendrite issue of Li metal anodes and the shuttle effect of polysulfides severely plague the safety and cycling stability of Li–S batteries. To address these problems, a novel nanoporous battery separator (MMMS) is designed based on an anionic metal–organic framework (MOF) UiO‐66‐SO3 Li and poly(vinylidene fluoride) (PVDF) following a mixed‐matrix membrane approach. Benefitting from the well‐defined anionic Li + transport tunnels across the MMMS, a homogeneous Li deposition is achieved to stabilize the plating/stripping cycling over 1000 h at a high current density of 5 mA cm −2 . Moreover, these tunnels featuring anionic electrostatic repulsion and a proper aperture size also demonstrate strong suppression to polysulfide shuttle and promote the redox activity and utilization of sulfur cathode material. With the MMMS to simultaneously promote the performance of Li metal anode and sulfur cathode, the Li–S battery delivers an elevated charge/discharge rate up to 5 C (552 mAh g −1 ) as well as a low capacity fading (0.056% per cycle at its steady stage) over 500 cycles at 0.5 C. Abstract : A metal–organic framework (MOF)‐based separator is designed for lithium–sulfur batteries. Decorated with abundant sulfonate anionic groups, the well‐defined nanotunnels in MOF crystals not only regulate homogeneous Li deposition but also suppress polysulfide shuttle, which simultaneously promotes the redox activity and cycling stability of lithium–sulfur batteries, from both Li metal anode and sulfur cathode aspects.